Assessing renewable energy readiness on military bases: a geospatial analysis of solar energy adoption in the West Coast Region of South Africa - Mathoho, Mashudu (Stellenbosch : Stellenbosch University, 2026)
Thesis (MMil)--Stellenbosch University, 2026.